Odpowiedzi

2013-07-05T13:06:03+02:00

 

a = 8cm

b = 6cm

c = 13cm

 

Ze wzoru Herona:

 

P = √p(p-a)(p-b)(p-c) gdzie p = 0,5(a+b+c)

 

p = 0,5(8cm + 6cm + 13cm) = 13,5cm

p-a = 13,5cm-8cm = 5,5cm

p-b = 13,5cm-6cm = 7,5cm

p-c = 13,5cm-13cm = 0,5cm

 

P = √13,5cm*5,5cm*7,5cm*0,5cm = 16,69cm²

 

----------------------------------------------------------------------------------------------------

Litterarum radices amarae sunt, fructus iucundiores

 

Pozdrawiam :)

  • Użytkownik Zadane
2013-07-05T13:07:32+02:00

Stosujemy tu wzór Herona:

P = √[p(p - a)(p - b)(p - c)]

 

a = 8cm   b = 6cm   c = 13cm

p = 1/2*(a  +b + c) = 1/2 * (8 + 6 + 13) = 1/2 * 27 = 13,5

 

P = √[13,5(13,5 - 8)(13,5 - 6)(13,5 - 13)]

P = √[13,5 * 5,5 * 7,5 * 0,5)

P = √278,4375

P = 16,6864... ~ 16,69cm²